Eurobarometer 43.1bis: Regional development and consumer and environmental issues, May-June 1995 - Reif, Karlheinz; Marlier, Eric; Commission of the European Communities (Commission of the European Communities, 1997)
This round of Eurobarometer surveys queried respondents on standard Eurobarometer measures such as public awareness of and attitudes toward the European Union (EU), and also focused on cross-border purchases, environmental protection, regional policies, and agriculture. Respondents were queried about what the Single European Market should mean, what consumer products they purchased from member countries, their satisfaction with products purchased from member countries, obstacles to buying and selling products to other member countries, and areas in which the EU has introduced measures to protect consumers. Environmental questions concerned whether respondents would support various proposals designed to fund the cost of cleaning up pollution, whether they felt information sources about the environment were truthful, and whether they would support.

Denna omgång av Eurobarometern innefattar bland annat generella frågor om allmänhetens kännedom och attityder till Europeiska unionen (EU). Enkäten fokuserar även på inköp över gränserna, miljöskydd, regionalpolitik och jordbruk. Respondenterna frågades om vad den europeiska inre marknaden, handel mellan medlemsländer och områden där EU har infört åtgärder för att skydda konsumenterna. De tillfrågades även om de skulle stödja olika förslag som syftar till att finansiera kostnader för sanering av föroreningar och om de ansåg att informationskällor om miljöfrågor var trovärdiga.
Eurobarometer 43.1bis: Regional development and consumer and environmental issues, May-June 1995
EB43.1bis
Keywords: Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Environment and conservation; Miljö och naturvård; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap